Guest Posted July 9, 2007 Report Share Posted July 9, 2007 1. a = b 2. a - b - 2 = a - b - 2 3. a(a - b - 2) = b(a - b - 2) 4. a2 - ab - 2a = ab - b2 - 2b 5. a2 - ab = ab - b2 - 2b + 2a 6. a2 - ab = ab + 2a - b2 - 2b 7. a(a - B) = a(b + 2) - b(b + 2) 8. a(a - B) = (a - B)(b + 2) 9. a = b + 2 10. b = b + 2 11. Thereforem 0 = 2 I have proven something similar with -10=any positive integer. I have since found this online and I am using the one I found and not my own. Quote Link to post Share on other sites

0 Guest Posted July 10, 2007 Report Share Posted July 10, 2007 If a=b then a-b=0 and therefore the factor (a-B) can not be used to simplify or reduce. Thanks Quote Link to post Share on other sites

0 Guest Posted July 10, 2007 Report Share Posted July 10, 2007 Here's a similar one to yours: x^2 - x^2= x^2 - x^2 => x(x-x)= (x-x)(x+x) => x=2x => 1=2 Thanks Quote Link to post Share on other sites

## Question

## Guest

1. a = b

2. a - b - 2 = a - b - 2

3. a(a - b - 2) = b(a - b - 2)

4. a2 - ab - 2a = ab - b2 - 2b

5. a2 - ab = ab - b2 - 2b + 2a

6. a2 - ab = ab + 2a - b2 - 2b

7. a(a - B) = a(b + 2) - b(b + 2)

8. a(a - B) = (a - B)(b + 2)

9. a = b + 2

10. b = b + 2

11. Thereforem 0 = 2

I have proven something similar with -10=any positive integer. I have since found this online and I am using the one I found and not my own.

## Link to post

## Share on other sites

## 2 answers to this question

## Recommended Posts

## Join the conversation

You can post now and register later. If you have an account, sign in now to post with your account.